Implementing Second Generation of costing system and its Impact on Costs Behavior Rationalization/ an Applied Study on the General Firm for the Pharmaceutical Industry and Medical Supplies/ Samarra - Hashim Mohammed, Hazim; Abdulaziz Mohsen, Mohammed (Zanco Journal of Human Sciences, 2023)
This research aims to verify the possibility of applying the driven-time activity-based cost system as a second generation and one of the modern management accounting methods as an input to determine the unused capacity and rationalize the cost behavior of the economic unity by testing this possibility if it is applied in the local environment. In this paper, the researchers used the practical approach to achieve the objectives of the study and test its hypotheses through the use of implementing a time-driven activity-based costing as a second-generation costing system on costs data in the General Firm for the Pharmaceutical Industry and Medical Supplies/Samarra's to separate unused capacity from the theoretical capacity as a applied aspect of the study. The research came out with many results, the most important of which is the time-driven activity-based costing system (TDABC), which separates the theoretical capacity, practical ability, and actual capacity in the research sample on the one hand, and on the other hand, the unused capacity costs come from the difference between theoretical capacity costs and actual capacity costs.